2012
DOI: 10.4269/ajtmh.2012.11-0694
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Serum Total IgE, IgG, and IgG1 Levels in Patients with and without Echinococcosis-Induced Anaphylactic Shock

Abstract: Abstract. We investigated serum total immunoglobulin E (IgE), IgG, and IgG1 levels in patients with and without echinococcosis-induced anaphylactic shock. This was a case-control study of 11 patients with echinococcosis-induced anaphylactic shock and 22 echinococcosis patients with cyst rupture but without anaphylactic shock. Blood was collected before surgery (T0), at the time of cyst rupture (T1), and shock (Tx), 1 h (T2), 1 day (T3), and 1 week (T4) after cyst rupture. Serum IgE, IgG, and IgG1 were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The relationship between IgE levels and a hydatid cyst is thought to be more pronounced in patients that exhibit complications of anaphylaxis (14). Guisantes et al (15) reported that the IgE levels decreased following surgery in patients with a hydatid cyst.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between IgE levels and a hydatid cyst is thought to be more pronounced in patients that exhibit complications of anaphylaxis (14). Guisantes et al (15) reported that the IgE levels decreased following surgery in patients with a hydatid cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the association of elevated IgE level made the diagnosis more difficult. Although elevated IgE is not specific for hydatid disease, but is present in a large subset of affected individuals [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…IgG is involved in anaphylactic shock or even death induced by antigens of parasites alongside IgE [ 14 , 21 ]. IgG accounts for about 75–80% of all immunoglobulins in the serum, and consists of 4 subtypes, IgG1, IgG2, IgG3, and IgG4 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of echinococcosis is relatively straightforward using various imaging methods [ 13 ], but it may be difficult to predict which patients will develop anaphylaxis [ 4 , 13 , 14 ]. In the present study, we retrospectively analyzed the clinical and immunological data of patients with echinococcosis who developed anaphylactic shock in the perioperative period to identify the associated factors and to provide some evidence for prevention and treatment of this complication.…”
Section: Introductionmentioning
confidence: 99%